City of Liverpool : Maternity and Child Welfare
1928-01 1928 1920s 5 pages Maternity and Child Welfare. Work at Infant Welfare Centres during January 1928, as per Returns received. P.2883.250.10/27.Est INFANT WELFARE CENTRES Day Nurseries. Infants' Consultations. Mothers' Consultations. Classes at Centres. Nourishment Provided. Visits to Infants from Corporation Centres. Visits under Notification of Births Act. Total Visits to Children. Visits to Mid-wives Cash received. Total Attendances New Cases Total Visits New Cases Total Visits Total Attendances Mothers Infants New Cases Total Visits. New Cases Under 1 year From 1 to 3 years From 3 to 5 years Total Re- visits 52, Earle Road 82 316 120 518 37a, Park Road 239 595 201, Rathbone Road 23 148 107. Boaler Street 167 567 81, St. Anne Street 314 506 251, Netherfield Road 241 531 366, Mill Street 76 228 Agents 144 563 NURSERIES. 264, Westminster Road 865 141/143, Smithdown Lane 687 Elm House. 415, Edge Lane 911 18, Gt. George Square 752 61, Shaw Street 566 Banks Road, Garston 549 63, Everton Road (Adam Cliff) 939 Health Visitors 1361 5598 2293 864 7088 Inspection of Midwives 183 Post-Natal Visits 225 Ophthalmia Neonatorum 36 364 328 5259 1286 3454 120 518 1397 5962 2293 864 7416 408 292/824/1/124-125